PREVALENCE OF HYPOKALEMIA IN PSYCHIATRIC INPATIENTS AT GRHASIA MENTAL HOSPITAL YOGYAKARTA - Krisniati, Theresia Rini; Zahra, Fathimah Az; Sefriyanto, Januarius Hendra Kurniawan; Amalia, Naila; Ardiningrum, Wikan (Departemen Psikiatri Fakultas Kedokteran Universitas Brawijaya, 2025)
Introduction: Hypokalemia, defined as a serum potassium level below 3.5 mEq/L, is often overlooked in psychiatric patients despite its clinical significance. Methods: This study examines the prevalence of hypokalemia in psychiatric inpatients at Grhasia Mental Hospital, Yogyakarta, from October to December 2023. A cross-sectional analysis of 365 patient records was conducted. Results: The majority (74.8%) were diagnosed with schizophrenia spectrum and other psychotic disorders. The overall prevalence of hypokalemia was 28.8%, with 4.9% of cases presenting with potassium levels below 3.0 mEq/L. Bivariate analyses using t-tests, ANOVA, and Pearson correlation showed no significant differences or correlations between serum potassium levels and demographic or clinical factors. Discuss: Almost one-third of the total psychiatric inpatients at Grhasia Mental Hospital in Yogyakarta experience hypokalemia. This prevalence rate is much higher compared to the general population, where hypokalemia occurs in only 2-5% overall. This high prevalence indicates that patients with mental disorders have a greater risk of experiencing electrolyte disturbances, which can affect their physical and mental condition. Conclusion: Given the high prevalence, routine electrolyte monitoring in psychiatric inpatients is essential to prevent complications. Further research is needed to explore the impact of antipsychotic medications on potassium regulation and to develop strategies for early detection and management of hypokalemia in psychiatric care.